2018
DOI: 10.1039/c8bm00010g
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular TSG-6 delivery from heparin-based microparticles reduces cartilage damage in a rat model of osteoarthritis

Abstract: As a potential treatment for osteoarthritis (OA), we have developed injectable and hydrolytically degradable heparin-based biomaterials with tunable sulfation for the intra-articular delivery of tumor necrosis factor-alpha stimulated gene-6 (TSG-6), a protein known to inhibit plasmin which may degrade extracellular matrix within OA joints. We first assessed the effect of heparin sulfation on TSG-6 anti-plasmin activity and found that while fully sulfated (Hep) and heparin desulfated at only the N position (Hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…Using 1 H NMR analysis, PEGDA was determined to be ~55% functionalized and Hep −N methacrylamide was determined to be 22-28% functionalized [36]. SAX-HPLC analysis was also used to assess Hep and Hep −N disaccharide composition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using 1 H NMR analysis, PEGDA was determined to be ~55% functionalized and Hep −N methacrylamide was determined to be 22-28% functionalized [36]. SAX-HPLC analysis was also used to assess Hep and Hep −N disaccharide composition.…”
Section: Resultsmentioning
confidence: 99%
“…Proton nuclear magnetic resonance ( 1 H NMR) was performed to determine the degree of PEGDA and Hep −N MAm functionalization, whereby each material was dissolved at 10 mg/mL in deuterated H 2 O (Sigma), run on a Bruker Avance III spectrometer at 400 Hz, and analyzed using iNMR software [33,36].…”
Section: Methodsmentioning
confidence: 99%
“…It is a multifunctional protein with anti-inflammatory and tissue-protective biopotencies [ 52 ]. It has been shown that intra-articular delivery of TNFAIP6 could reduce cartilage damage in a rat model of OA [ 53 ]. However, in the current study, the expression of TNFAIP6 is increased in both cartilage and synovium tissue during OA.…”
Section: Discussionmentioning
confidence: 99%
“…Cartilage damage due to injury or disease may cause loss of joint function. Currently prescribed drugs such as TSG‐6 and NSAIDs can only delay the deterioration and relieve the symptoms, but cannot promote tissue restoration . Cartilage lacks the ability to self‐repair and hence cartilage restoration is an important clinical goal .…”
Section: Hydrogel Scaffold For Regenerative Medicinementioning
confidence: 99%